Evaluating economic value added of SFIs in Thailand using CAMEL Model - Krittidesh Wongpool; Supasith Chonglerttham; Zimmermann, Willi; Sununta Siengthai; HM King Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
This research studies "The Relationship between the CAMEL model and Economic Value Added: A Case study of the SFIs in Thailand". The main objectives of this research were to assess the financial performance of four Specialized Financial Institutions (SFIs) by using the CAMEL model and Economic Value Added (EVA) concept, and to analyze the relationship between the CAMEL model and Economic Value Added of four SFIs consisting of the Government Savings Bank, the Government Housing Bank, the Bank for Agriculture and Agricultural Co-operatives, and the Islamic Bank of Thailand during 2006 to 2015. After compiling financial data and information from SFIs' annual reports and financial statements, the calculation and analysis of the research were made by applying Kendall tua-b Correlation Coefficient and Multiple Regression Analysis. The outcome of the research indicates that the relationship, by using the Multiple Regression Analysis, between the CAMEL model and Economic Value Added (EVA) ofthe 4 SFIs is existing, 4 ratios are the equity capital to asset ratio, the loan charge-offs to gross loan ratio, the net interest margin ratio, and the primary assets to deposits ratio can statistically explain the change of variables or the EVA of four SFIs significantly. Key words: CAMEL model, Economic Value Management (EVM) , Value Based Management (VBM), Economic Value Added (EVA), Net Operating Profit After Taxes (NOPAT), Weighted Average Cost of Capital (W ACe), Capital Charge, Specialized Financial Institutions (SFls), Capital Employed
A research submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in Business Administration
Research report (M. BA.) - Asian Institute of Technology, 2017
Keywords: Economic value added -- Evaluation; Economic value added -- Management